(2a+b)平方-2(4a平方-b平方)+(2a-b)平方 已知:x²+4x+y²-6y+13=0,求x+y的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 00:48:32
(2a+b)平方-2(4a平方-b平方)+(2a-b)平方已知:x²+4x+y²-6y+13=0,求x+y的值(2a+b)平方-2(4a平方-b平方)+(2a-b)平方已知:x
(2a+b)平方-2(4a平方-b平方)+(2a-b)平方 已知:x²+4x+y²-6y+13=0,求x+y的值
(2a+b)平方-2(4a平方-b平方)+(2a-b)平方 已知:x²+4x+y²-6y+13=0,求x+y的值
(2a+b)平方-2(4a平方-b平方)+(2a-b)平方 已知:x²+4x+y²-6y+13=0,求x+y的值
(2a+b)平方-2(4a平方-b平方)+(2a-b)平方
已知:x²+4x+y²-6y+13=0,求x+y的值
这个是两道题吧
前面好像没问题呢.
后面这个(x+2)²+(y-3)²=0
x=-2 y=3 x+y=1
(2a+b)²-2(4a²-b²)+(2a-b)²
用完全平方公式分解因式:
原式=(2a+b)²-2(2a+b)(2a-b)+(2a-b)²
=[(2a+b)-(2a-b)]²
=b²
x²+4x+y²-6y+13=0
(x²+4x+4)+(y²-6y+9)=0
(x+2)²+(y-3)²=0
x=-2,y=3
x+y=-2+3=1
a平方-4b平方-a+2
(a平方-b平方)/(a-b) +(2a平方-4ab+2b平方)/(a-b)平方
a平方b-[a平方b-(2abc-a平方c-3a平方b)-4a平方c]-abc
(a平方-b平方)平方+(a平方+2b平方)平方
(a平方+b平方)平方-(2ab)平方 因式分解
(a平方+b平方)的平方-2(a平方+b平方)=8,求a平方+b平方
(2a-b)平方-b平方
(a-3)平方-(2a-b)平方
化简(4a平方-3b平方)-【2(2a平方-1)+2b平方-3】
计算:(a平方-2b平方+4)(a平方+2b平方-4)
(a平方-2b平方+4)(a平方+2b平方-4)
4(a的平方b-2ab平方)-(a平方b+2ab平方)
4(a的平方b-2ab平方)-(a平方b+2ab平方)?
a的平方b-(-3ab平方)+(-4a平方b)-2ab平方=
a平方+b平方+1+ab^2=4ab、求a平方+b平方
a平方+b平方)-4a平方b平方
因式分解 (4a平方-b平方)/(b-2a)
4(a+2b)平方-25(a-b)平方